Hollywood, Home Movies, and Common Sense. Aesthetic Control - Zimmermann, Patricia Rodden (Iluminace, 2004)
The practice of amateur family filmmaking, the most frequent topics, the development of family film from 1950 to the present and the basic points of the theoretical approach to family film.
Keywords: amateur film; home video; film theory; family film history